Big Data & eLearning: A Binomial to the Future of the Knowledge Society - Alonso Secades, Vidal; Arranz, Olga (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
There is no doubt that in what refers to the educational area, technology is producing a series of changes that will greatly affect our near future. The increase of students experiences in the new educational systems in distance learning makes possible to have information related to the students ‘activities and how these can be dealt with automatic procedures. The implementation of these analytical methods is possible through the use of powerful new technologies such as Data Mining or Big Data. Relevant information is obtained of the use made by the students of the technological tools in a Learning Management System, thus, allowing us to infer a pattern of behavior of the students, to be used in the future.
Keywords: e-learning; education; technology enhanced; big data; learning analytics; IJIMAI